Chemical Composition, Fatty Acid Profile, And Amino Acid Profile of Sahoaki (Tripneustes Gratilla) Gonads From Sangihe Island, Indonesia - Ni Wayan Suriani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Sahoaki (Tripneustes gratilla), abundant in Sangihe Island, is a food ingredient by local people. This study aims to determine the chemical composition, fatty acid profile (bioactive content of omega-3, omega-6, and omega-9 fatty acids), and amino acid profile of the sahoaki gonads from Sangihe Island, Indonesia. The fatty acid profile was tested using the Gas Chromatography method (GC 7890B), while the amino acid profile was tested using Liquid chromatography-mass spectrometry. The results of research on fresh sahoaki gonads showed that the chemical composition: water content (84.24 and 85.99)%, fat (3.77 and 2.67)%, protein (10.12 and 9.34)%, carbohydrates (0.08 and 0.05)%, and ash (3.19 and 2.95)%. Fatty acid profile: there are 14 saturated fatty acid profiles, seven monounsaturated fatty acid profiles, nine polyunsaturated fatty acid profiles, the total content of omega-3 (19.46 and 15.95%), omega-6 (16.25 and 16, 39 %), and omega-9 (12.94 and 13.94%). Seven amino acid profiles were detected, consisting of five essential amino acids and two non-essential amino acids. Sahoaki gonads have good nutritional value because they contain high omega-3, Omega-6, and Omega-9 fatty acids and are equipped with essential amino acids, which have the potential as functional food ingredients.